Serum HMGB1 and hs-CRP levels in adolescents with ADHD: a preliminary case-control study - Fatma Subaşı Turgut; Yağmur Soysal; Neval Kızıl; Masum Öztürk; Sevgi Gökcüoğlu Nakipoğlu; Revşa Evin Canpolat Erkan; Mahmut Bulut (Academic Journal of Health Sciences, 2026)
Background: This study aimed to compare serum high mobility group box-1 (HMGB1) and high-sensitivity C-reactive protein (hs-CRP) levels in individuals diagnosed with attention-deficit/hyperactivity disorder (ADHD) with those of a control group. Methods: The study included adolescents aged 12–18 years diagnosed with ADHD and healthy controls. Diagnostic assessment was performed using the K-SADS-PL interview; ADHD symptom severity was evaluated with the Turgay DSM-IV Disruptive Behavior Disorders Rating Scale (T-DSM-IV-S), and autism-like symptoms were assessed with the ASSQ. Serum HMGB1 and hs-CRP levels were measured by ELISA. Results: Serum HMGB1 levels in the ADHD group (21.17 ± 12.17 ng/mL) were significantly lower compared to the control group (36.37 ± 21.88 ng/mL) (p < 0.001). In contrast, hs-CRP levels did not differ between the groups (p = 0.888). No significant association was found between HMGB1 and ADHD symptom severity; however, a significant positive correlation was identified with the ASSQ communication problems subscale (r = 0.401, p = 0.013). ROC analysis revealed moderate discriminative power (AUC = 0.738, cut-off value = 24.50 ng/mL; sensitivity 68.9%, specificity 74.3%). Conclusions: Serum HMGB1 levels were lower in adolescents with ADHD than in healthy controls, whereas hs-CRP levels did not differ between groups. The association between HMGB1 and communication problems suggests a possible relationship with specific neurodevelopmental dimensions; however, these findings are preliminary and hypothesis-generating and require replication in larger pediatric samples.